2022
DOI: 10.3390/ijms23158210
|View full text |Cite
|
Sign up to set email alerts
|

Cellular and Molecular Mechanism of Pulmonary Fibrosis Post-COVID-19: Focus on Galectin-1, -3, -8, -9

Abstract: Pulmonary fibrosis is a consequence of the pathological accumulation of extracellular matrix (ECM), which finally leads to lung scarring. Although the pulmonary fibrogenesis is almost known, the last two years of the COVID-19 pandemic caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) and its post effects added new particularities which need to be explored. Many questions remain about how pulmonary fibrotic changes occur within the lungs of COVID-19 patients, and whether the changes will pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 112 publications
0
17
0
Order By: Relevance
“…Due to the rapidly evolving COVID-19 pandemic, Gas6/TAM axis activation has gained interest due to its involvement in inflammatory responses and subsequent fibrosis, two features strictly related to severe SARS-CoV-2 clinical manifestations [ 28 ].…”
Section: Physiological Role Of the Gas6/tam Axis: An Overviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the rapidly evolving COVID-19 pandemic, Gas6/TAM axis activation has gained interest due to its involvement in inflammatory responses and subsequent fibrosis, two features strictly related to severe SARS-CoV-2 clinical manifestations [ 28 ].…”
Section: Physiological Role Of the Gas6/tam Axis: An Overviewmentioning
confidence: 99%
“…A fine and timely regulation of fibrotic response is necessary to support physiological wound healing: as discussed for inflammation, also in the case of fibrosis, a de-regulated response could result in a negative clinical evolution, with diffuse fibrosis impairing the physiological activities of the involved tissues. In particular, fibrosis is triggered by virtually all types of insults and affects all organs and tissues [ 28 , 36 ]. Moreover, in virtually all progressive chronic diseases, fibrosis becomes irreversible over time, thus accounting for a progressive loss of functionality of the involved tissue [ 37 , 38 ].…”
Section: Gas6/tam Axis Role In Modulating Fibrotic Evolutionmentioning
confidence: 99%
“…The correlation of N-cleaved-Gal9 levels with sIL-2R levels in the recovery phase may indicate an involvement of cleaved-Gal-9 in persistent inflammation. Gal-9 can be implicated in the process of post-ARDS lung fibrosis in COVID-19 [ 48 ]. However, we observed that the patients did not present pulmonary fibrosis after TCZ treatment in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, Gal-8 has also been suggested to have disparate roles in immunity, functioning as an enhancer of the expression and secretion of many pro-inflammatory cytokines or as a cytokinebinding partner to sequester and hinder cytokine activity (12). For this reason, galectins have been linked to a variety of inflammatorydriven disorders (e.g., cancer, cardiovascular, and metabolic diseases) (11)(12)(13)(14)(15)(16). Moreover, since these molecules are also involved in pro-fibrotic processes (13), their role is particularly relevant because they are involved in the pathogenesis of several disorders affecting several organs including the heart and lungs (16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, galectins have been linked to a variety of inflammatorydriven disorders (e.g., cancer, cardiovascular, and metabolic diseases) (11)(12)(13)(14)(15)(16). Moreover, since these molecules are also involved in pro-fibrotic processes (13), their role is particularly relevant because they are involved in the pathogenesis of several disorders affecting several organs including the heart and lungs (16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%